WHAT DO THEY VALUE? INVESTIGATING LIBRARIANS’ ATTITUDES TOWARD CONTINUING PROFESSIONAL DEVELOPMENT PURSUITS - Abrigo, Christine M.; Abrigo, Vincent M. (Journal of Philippine Librarianship; Vol 37 (2017), 2019)
This paper primarily investigates the librarians’ attitude in their participatory decisions when it comes to their continuing professional development (CPD) engagements, which would eventually contribute to their learning and relevance as a library and information professional. Since quite a number of local research gave focus on competencies, kinds and benefits of CPD pursuits, the intention of the paper is for librarians to look beyond the material and legalistic benefits of CPD initiatives and opportunities, especially in light of the ASEAN economic integration. Using the concept of adult education learning, the study attempts to examine the values librarians attach to determine their professional and personal learning direction. Results of the study point towards understanding the respondents' conscious efforts in their professional upkeeping, and how they value CPD participation to further develop their expected learning outcomes. It is anticipated that the study will have potential contribution along with the current efforts to strengthen CPD programs in the Philippines.
Keywords: continuing professional development, attitudes, values, participation